A Case of Late-onset Hyperinsulinemic Hypoglycemia: HNF4A Mutation - Gülçin Arslan; Sezer Acar; Taha Reşid Özdemir; Özlem Nalbantoğlu; Özgür Kırbıyık; Özge Köprülü; Beyhan Özkaya; Behzat Özkan (Journal of Pediatric Research)

(untitled)
Hyperinsulinemic hypoglycemia is a rare disease affecting infants and children. The frequency of HNF4A mutation is the third most common type following ABCC8 and KCNJ11 mutations. HNF4A inactivating mutations may cause hyperinsulinemic hypoglycemia generally in the neonatal period by impairing insulin production and the secretion in pancreatic  cells. Herein, we present a case of an 8-month-old girl with hyperinsulinemic hypoglycemia who had normal birth weight. In this case, hypoglycemia became prominent after acute gastroenteritis and long-term glucose infusion was administrated to overcome hypoglycemia. On follow up, diazoxide treatment up to 12 mg/kg/day was required to achieve normal glucose levels. In the molecular genetic analysis, a heterozygous mutation was found in the HNF4A gene (c.266G> A, p.R89Q), which was previously described in a case with MODY (maturity-onset diabetes of the young) type 1. During two weeks of hospitalization, while the glucose infusion rate was tapered, oral feeding was increased. Diazoxide treatment continued after discharge and was gradually stopped when she was at the age of 14 months. Afterwards, no hypoglycemia was observed. HNF4A gene mutation should be kept in mind even if there is no macrosomia or family history of diabetes in patients presenting with hypoglycemia and requiring diazoxide therapy.